Measuring quality of life in patients with head and neck cancer: update of the EORTC QLQ-H&N Module, Phase III - Singer, Susanne; Araújo, Cláudia; Arraras, Juan Ignacio; Baumann, Ingo; Boehm, Andreas; Herlofson, Bente Brokstad; Silva, Joaquim Castro; Chie, Wei-Chu; Fisher, Sheila; Guntinas-Lichius, Orlando; Hammerlid, Eva; Irarrázaval, María Elisa; et al. (Head & neck, 2015)
Background The objective of this study was to pilot test an updated version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Head and Neck Module (EORTC QLQ-H&N60). Methods Patients with head and neck cancer were asked to complete a list of 60 head and neck cancer-specific items comprising the updated EORTC head and neck module and the core questionnaire EORTC QLQ-C30. Debriefing interviews were conducted to identify any irrelevant items and confusing or upsetting wording. Results Interviews were performed with 330 patients from 17 countries, representing different head and neck cancer sites and treatments. Forty-one of the 60 items were retained according to the predefined EORTC criteria for module development, for another 2 items the wording was refined, and 17 items were removed. Conclusion The preliminary EORTC QLQ-H&N43 can now be used in academic research. Psychometrics will be tested in a larger field study. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1358-1367, 2015